PENINGKATAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN PEMBELAJARAN MAKE- A MATCH PADA MATA PELAJARAN IPS KELAS V SD NEGERI 013 KECAMATAN PERANAP INDRAGIRI HULU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
This study was conducted in class V SDN 013 District of Peranap Indragiri Hulu,this study came from low yields social studies history with an average of 45% (Enough). Toovercome this problem, the authors apply the learning to Make A- Match. Therefore, theformulation of this problem is: Is there an increase in student learning outcomes through the useof learning to Make A- Match SDN 013 District of Peranap Indragiri Hulu?This study aims to pinpoint the impact and results of social studies in the fifth grade students ofSDN 013 District of Peranap Indragiri Hulu.Hope authors of this study can be useful for writers, schools and students.The results of the study in the first cycle shows that by using the Make A-Match learning learningoutcomes increased from 45% (enough) to 60.9 (Pretty Good), while discipline students achievedan average 68% The results of this study have not yet reached the target of 75 %, therefore, theauthors continued in the second cycle. The result is an increase in learning outcomes of 60.9(Pretty Good) in the first cycle to 71.6% (good) on the second cycle. The discipline of studentsincreased to an average of 73.6%. Learning takes place in accordance with the expected activeand creative students find learning the core material.Keywords: student learning, use of Learning Make A Macth